2001
DOI: 10.1089/105072501300176381
|View full text |Cite
|
Sign up to set email alerts
|

Iodine and Thyroid Autoimmune Disease in Animal Models

Abstract: Thyroid autoimmune diseases are complex, polygenic afflictions the penetrance of which is heavily dependent on various environmental influences. In their pathogenesis, an afferent stage (enhanced autoantigen presentation), a central stage (excessive expansion and maturation of autoreactive T and B cells), and an efferent stage (effects of autoreactive T cells and B cells on their targets) can be discerned. At each stage, a plethora of inborn, endogenous or exogenous factors is able to elicit the abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 52 publications
2
35
1
5
Order By: Relevance
“…Furthermore, we could not detect proliferative cell responses of NOD.H2 h4 spleen cells to A k -restricted T cell epitopes of Tg most of which are known to induce thyroiditis either as iodinated 17,20 or non-iodinated peptides. 17,21 Our inability to demonstrate formation of I-Tg in this ISAT model is seemingly at odds with the results of numerous EAT studies 6,11,19,31,32 attributing a critical role for Tg iodination in the disease process. In several studies, iodine-depleted Tg does not activate thyroiditogenic T cells but, by raising the Tg iodine content to normal levels in vitro, the immunopathogenicity of the molecule is re-established.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, we could not detect proliferative cell responses of NOD.H2 h4 spleen cells to A k -restricted T cell epitopes of Tg most of which are known to induce thyroiditis either as iodinated 17,20 or non-iodinated peptides. 17,21 Our inability to demonstrate formation of I-Tg in this ISAT model is seemingly at odds with the results of numerous EAT studies 6,11,19,31,32 attributing a critical role for Tg iodination in the disease process. In several studies, iodine-depleted Tg does not activate thyroiditogenic T cells but, by raising the Tg iodine content to normal levels in vitro, the immunopathogenicity of the molecule is re-established.…”
Section: Discussionmentioning
confidence: 78%
“…Jodo stygius susilpnina linkusiems į autoimunitetą žmonėms autoimuninio tiroidito pasireiškimą. Ir priešingai, jodo perteklius pagreitina tokiems žmonėms Hašimoto tiroidito pasireiškimą, taip pat pablogina ligos procesą, nes dėl padidėjusio tiroglobulino jodavimo palengvėja paslėpto, patogeninio peptido selektyvus apdorojimas ir pristatymas T ląstelei (39).…”
Section: Jodas Ir Vaistaiunclassified
“…In very severe iodine deficiency, stunted growth and mental retardation can occur in children (Laurberg, 2004). A number of studies have reported adverse effects on hearing capacity, motor and cognitive function in children associated with moderate and severe iodine deficiency (Venturi et al, 2000;Ruwhof and Drexhage, 2001;Mann and Aitken, 2003).…”
Section: Introductionmentioning
confidence: 99%